Was Feuerbach right: are we what we eat? - Cizza, Giovanni (American Society for Clinical Investigation, 2011)
Food and stress are powerful modulators of the body-mind connection, which is imbalanced in obese individuals. Why do we choose chocolate over an apple when overworked and stressed, and why does comfort food make us feel better? Two independent studies in the JCI, one in this issue, home in on the role of stress on gut hormones and food choices and, conversely, on the effect of the intestinal system on modulation of brain activity by sadness. These studies broaden our understanding of the ties between food and mood and underscore promising targets for obesity treatments.